Physiological and psychological effects of visits to different linear Spatial landscape on the students: a field experiment in the campus environment - Ren-Lin Zhao; Lu-Qi Bai; Yu-Lin Zhao; Yi-Tian Zhou; Meng Luo (Journal of Health, Population and Nutrition)
Abstract Background There is now a substantial body of evidence supporting the positive impact of urban green spaces on human health and well-being. Most studies in this field have primarily focused on various types of green landscapes. However, there remains a notable gap in research regarding specific green spaces, particularly those associated with linear spatial landscapes, such as pathway spaces. The purpose of this study is to explore the restorative effects of the different types of linear spaces within the campus environments on the students’ physical and mental health. Methods We investigated psycho-physiological responses of the participants in each group (N = 40, 20 ± 2.4 years old) to the environments of pre- and post-visiting the different pathway spaces, including avenue passage space (APS), gallery frame passage space (GPS), waterfront road passage space (WPS), driveway passage space (DPS), and indoor corridor passage space (IPS) (Control group). Physiological factors were examined using heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and psychological evaluation was carried out using the Profile of Mood States (POMS), State-Trait Anxiety Inventory (STAI), and the Perceived Restorative Scale (PRS). Results The results indicated that SBP, DBP, and HR levels of participants were significantly reduced after visiting APS, FPS, and WPS, whereas remarkable increases in HR were observed in the DPS. The POMS scores for anger-hostility (A-H), fatigue-inertia (F-I), tension-anxiety (T-A), confusion-bewilderment (C-B), and depression-dejection (D-D) were significantly lower, but vigor-activity (V-A) was higher post-visiting than pre-visiting. Furthermore, the participants exhibited significantly reduced anxiety levels and high psychological restoration levels, as indicated by the STAI and PRS. Importantly, the most pronounced changes in measurement indices were observed in the GPS. Conclusions Our study demonstrates that exposure to linear spatial landscapes, particularly those featuring abundant landscape elements, safety features, and shelter, such as GPS, holds potential as a therapeutic method for improving physiological functions and as an effective psychological relaxation strategy for students in campus environments.